Acoustic reinforcing material, preparation method thereof, loudspeaker and electronic equipment

By combining the fiber-like structure-reinforced filler-reinforced silica aerogel with SSZ-13 zeolite molecular sieve to form an acoustic reinforcement material with regular pore structure, the problem of performance degradation caused by adsorption of small organic molecules in existing porous materials is solved. And significantly improve the low-frequency acoustic effect.

CN119431002AActive Publication Date: 2025-02-14SHANGHAI JIAOTONG UNIV +1

Patent Information

Application Number
CN202411390402.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-14
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The polymer adhesive introduced by existing porous materials during the molding process will cause small organic molecules to evaporate and be adsorbed, blocking the pore structure, causing acoustic performance to decline, and the pore distribution of amorphous materials is difficult to control.

Method used

The silica aerogel reinforced with a fibrous structure reinforced filler is combined with the SSZ-13 zeolite molecular sieve to form an acoustic reinforced material through chemical bonding, ensuring that the pore structure of the material has regular micropores, mesoporous and macropore distribution.

Benefits of technology

The low-frequency acoustic improvement effect of acoustic reinforced materials is achieved, the performance degradation caused by adsorption of organic small molecules is avoided, and the porosity and specific surface area of ​​the material are improved through regular pore structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431002A_ABST
    Figure CN119431002A_ABST
Patent Text Reader

Abstract

The invention provides an acoustic reinforcing material and a preparation method thereof, a loudspeaker and electronic equipment, the acoustic reinforcing material has micropores, mesopores and macropores, and comprises silica aerogel reinforced by fibrous structure reinforcing filler and an SSZ-13 zeolite molecular sieve, the SSZ-13 zeolite molecular sieve is combined with the inside and the surface of the silicon dioxide aerogel reinforced by the fibrous structure reinforcing filler through chemical bonds. The acoustic reinforcing material provided by the invention has an excellent low-frequency acoustic improvement effect, relatively high strength, relatively low water absorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an acoustic enhancement material and a preparation method thereof, a loudspeaker and an electronic device, and belongs to the technical field of materials, in particular to the technical field of electronic acoustic materials. Background Art

[0002] Miniaturization of speakers has become a mainstream trend and has attracted more and more attention. However, the acoustic quality of micro speakers deteriorates as the size decreases. Porous materials have a very high specific surface area and have a good adsorption-storage-desorption effect on air molecules. They are often used in micro speakers to improve low-frequency acoustic effects. When the speaker diaphragm vibrates, the pressure in the back cavity of the speaker changes, thereby compressing the air and allowing it to enter the porous material. When the pressure decreases, the air molecules adsorbed and stored in the porous material are released, thereby changing the rigidity of the air in the back cavity of the speaker and improving the low-frequency acoustic effect.

[0003] CN103098490A discloses a zeolite molecular sieve with a silicon-aluminum mass ratio of more than 200 as a speaker low-frequency improvement material, wherein the zeolite molecular sieve is formed into 0.2-0.9mm particles by an organic adhesive. The particles contain pore structures of different sizes and can achieve a good acoustic improvement effect; however, the introduction of organic adhesives will lead to the generation of volatile organic small molecules during long-term operation. If these organic small molecules cannot be discharged in time, they will be adsorbed by the zeolite molecular sieve in the particles, and part of the pore structure in the particles will be blocked, reducing its acoustic improvement effect.

[0004] CN109874089A discloses using SiO2 aerogel as a sound-absorbing material to improve the acoustic effect of a speaker; the sound-absorbing material contains pore structures such as mesopores and micropores. When a high molecular polymer binder is introduced, there is also the problem of organic volatile small molecules blocking the pore structure; in addition, SiO2 aerogel is an amorphous porous material, and the proportion of its micropores, mesopores, and macropores is difficult to control, and there is a lot of randomness in the synthesis process.

[0005] In summary, in the prior art, the polymer adhesive introduced into the porous material during the molding process will produce volatile organic small molecules during long-term operation. The organic small molecules are easily adsorbed by the porous material, blocking the pore structure and causing performance degradation; in addition, the pore distribution of amorphous materials is difficult to control.

[0006] Therefore, providing a new type of acoustic enhancement material and a preparation method thereof, as well as a loudspeaker and an electronic device has become a technical problem that urgently needs to be solved in the field. Summary of the invention

[0007] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide an acoustic enhancement material.

[0008] Another object of the present invention is to provide a method for preparing the above-mentioned acoustic enhancement material.

[0009] Another object of the present invention is to provide a speaker, wherein at least one of the speaker front cavity, speaker rear cavity, housing and sound-emitting unit is equipped with the acoustic enhancement material described above.

[0010] Another object of the present invention is to provide an electronic device comprising the above-mentioned speaker.

[0011] In order to achieve the above objectives, on the one hand, the present invention provides an acoustic enhancement material, wherein the acoustic enhancement material has micropores, mesopores and macropores at the same time, and includes silica aerogel reinforced with a fibrous structure reinforcing filler and SSZ-13 zeolite molecular sieve, and the SSZ-13 zeolite molecular sieve is bonded to the interior and surface of the silica aerogel reinforced with the fibrous structure reinforcing filler through chemical bonds (chemical bonds formed during the crystallization process).

[0012] As a specific embodiment of the acoustic enhancement material described above in the present invention, the mass ratio of the SSZ-13 zeolite molecular sieve to the silica aerogel reinforced with the fibrous structure reinforcing filler is 1:1-1:4.

[0013] As a specific embodiment of the acoustic enhancement material described above in the present invention, the SSZ-13 zeolite molecular sieve includes pure silicon structure molecular sieve, silicon aluminum structure molecular sieve, silicon phosphorus aluminum structure molecular sieve or phosphorus aluminum structure molecular sieve, etc. In order to ensure that the molecular sieve material has a strong binding force with the silica aerogel reinforced with the fibrous structure reinforcing filler, the constituent elements of the molecular sieve material preferably contain silicon element, that is, preferably, the SSZ-13 zeolite molecular sieve is pure silicon structure molecular sieve, silicon aluminum structure molecular sieve or silicon phosphorus aluminum structure molecular sieve, etc.

[0014] When the SSZ-13 zeolite molecular sieve is selected from non-pure silicon structure molecular sieves such as silicon-aluminum structure molecular sieve, silicon-phosphorus-aluminum structure molecular sieve or phosphorus-aluminum structure molecular sieve, the present invention does not specifically limit the molar ratio of silicon and metal in the SSZ-13 zeolite molecular sieve, such as the silicon-aluminum ratio. For example, when the SSZ-13 zeolite molecular sieve is a silicon-aluminum structure molecular sieve, considering that the SSZ-13 zeolite molecular sieve with a lower silicon-aluminum ratio has a good affinity for water molecules, therefore, in order to make the acoustic enhancement material have excellent anti-water absorption, it is possible to consider using a SSZ-13 zeolite molecular sieve with a relatively high silicon-aluminum ratio (the molar ratio of silicon-aluminum atoms is not less than 100) in practical applications.

[0015] In addition, for the silicon-aluminum structure molecular sieve, due to the requirement of structural electrical neutrality, cations outside the framework can be introduced, and the cations outside the framework can be one or a combination of hydrogen ions, monovalent metal ions, divalent metal ions and multivalent metal ions. The present invention does not make specific requirements on the method of introducing cations outside the framework of the silicon-aluminum structure molecular sieve, and the specific introduction method can be reasonably selected according to the actual operation needs on site and / or the specific substances of the cations, as long as it can ensure that the purpose of introducing cations outside the framework of the silicon-aluminum structure molecular sieve can be achieved.

[0016] As a specific embodiment of the acoustic enhancement material described above, the total weight of SiO2 in the silica aerogel reinforced with the fibrous structure reinforcing filler is 100%, and the content of the fibrous structure reinforcing filler is 1-8%. Too high a content of the fibrous structure reinforcing filler will increase the water absorption rate of the acoustic enhancement material, thereby affecting its acoustic performance.

[0017] As a specific embodiment of the acoustic enhancement material described above in the present invention, the silica aerogel reinforced with the fibrous structure reinforcing filler comprises a fibrous structure reinforcing filler and silica aerogel, and the fibrous structure reinforcing filler is uniformly dispersed in the silica aerogel.

[0018] As a specific embodiment of the acoustic enhancement material described above, the size of the silica aerogel reinforced with the fibrous structure reinforcing filler is 35-50 meshes.

[0019] As a specific embodiment of the acoustic enhancement material described above in the present invention, the fibrous structure reinforcement filler includes one or a combination of halloysite, boehmite, mullite and asbestos.

[0020] The present invention does not make specific requirements on the morphology of the acoustic enhancement material. The silica aerogel reinforced with the fibrous structure reinforcement filler can present different appearances, and can select a suitable specific form according to the use requirements (such as the speaker back cavity form). For example, its appearance can be an irregular form, such as irregular particles, irregular blocks, irregular sheets, irregular fibers and irregular polyhedrons, etc., or a regular form, such as regular spherical particles, nearly spherical regular particles, regular blocks, regular sheets and regular fibers, etc., or a combination of one or more. In some embodiments, large-sized acoustic enhancement materials can be formed by bonding the prepared nano-micro superstructure particles, that is, smaller-sized acoustic enhancement materials.

[0021] On the other hand, the present invention also provides a method for preparing the above-mentioned acoustic enhancement material, wherein the preparation method comprises:

[0022] Dissolving a silicon source, an alkali source and a mineralizer in deionized water to obtain a molecular sieve mother liquor;

[0023] The silica aerogel reinforced with a fibrous structure reinforcing filler is added to the molecular sieve mother solution and mixed evenly, the obtained mixed solution is crystallized, and finally the crystallized product is washed, dried and calcined to obtain the acoustic enhancement material.

[0024] As a specific embodiment of the preparation method described above, the molecular sieve mother solution further contains a template. The silica aerogel reinforced with a fibrous structure reinforced filler has good thermal stability, and the structure of the silica aerogel is not destroyed even in the process of introducing the template and subsequently burning the template at high temperature.

[0025] As a specific embodiment of the preparation method described above, the calcination temperature is not higher than 700°C. In addition, the present invention does not make specific requirements on the specific substances of the silicon source, alkali source, mineralizer and template used in the preparation of the acoustic enhancement material, as well as their respective amounts, and can be reasonably selected and adjusted according to actual needs on site. For example, in some embodiments of the present invention, the template can be selected from N,N,N-trimethyl-1-adamantyl ammonium hydroxide, etc.

[0026] As a specific embodiment of the preparation method described above in the present invention, the preparation method of the silica aerogel reinforced with the fibrous structure reinforcing filler comprises:

[0027] A silicon source, a co-solvent and deionized water are mixed to obtain a first mixed liquid, an acidic catalyst is added to the first mixed liquid to hydrolyze the silicon source to produce a sol, a gel accelerator and a fibrous structure reinforcing filler are then added to the sol and mixed evenly to obtain a second mixed liquid, an alkaline catalyst is then added to the second mixed liquid to form a wet gel, and finally the wet gel is aged and dried to obtain the silica aerogel reinforced with the fibrous structure reinforcing filler.

[0028] As a specific embodiment of the preparation method described above in the present invention, the silicon source used in preparing the silica aerogel reinforced with fibrous structure reinforcing fillers is organic silicon and / or inorganic silicon, wherein the organic silicon includes one or a combination of tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), polysiloxane (PEDS), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES) and silsesquioxane (POSS), and the inorganic silicon includes one or a combination of silica sol, water glass, sodium silicate and silicon tetrachloride.

[0029] As a specific embodiment of the preparation method described above in the present invention, the acid catalyst used in the preparation of the silica aerogel reinforced with a fibrous structure reinforcing filler is an organic acid catalyst and / or an inorganic acid catalyst, wherein the organic acid catalyst includes one or a combination of formic acid, acetic acid, oxalic acid, propionic acid, malonic acid, succinic acid, glutaric acid, citric acid, monosodium citrate, oleic acid and oxalic acid, and the inorganic acid catalyst includes one or a combination of hydrochloric acid, bromic acid, boric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, phosphoric acid, phosphorous acid, metaphosphorous acid, ammonium bisulfate, sodium bisulfate, potassium bisulfate, ferric acid and permanganic acid.

[0030] As a specific embodiment of the preparation method described above in the present invention, the alkaline catalyst used in the preparation of the silica aerogel reinforced with a fibrous structure reinforcing filler is an organic alkaline catalyst and / or an inorganic alkaline catalyst, wherein the organic alkaline catalyst includes one or a combination of methylamine, ethylamine, ethylenediamine, propylamine, propylenediamine, isopropylamine, diisopropylamine, butylamine, cyclohexylamine, hexamethylenediamine, melamine and imidazole, and the inorganic alkaline catalyst includes one or a combination of ammonia water, hydrazine hydrate, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, potassium oxalate, sodium oxalate, sodium formate and sodium acetate.

[0031] As a specific embodiment of the preparation method described above in the present invention, the cosolvent used in preparing the silica aerogel reinforced with fibrous structure reinforcing fillers includes one or a combination of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, butanol and butanediol.

[0032] As a specific embodiment of the preparation method described above of the present invention, the gel accelerator used in preparing the silica aerogel reinforced with fibrous structure reinforcing fillers includes one or a combination of formamide, acetamide, methylacetamide, methylenediformamide, terephthalamide and phthalamide.

[0033] As a specific embodiment of the preparation method described above of the present invention, when preparing the silica aerogel reinforced with fibrous structure reinforcing fillers, the temperature of the hydrolysis process is 40-80° C. and the time is 2-48 hours.

[0034] As a specific embodiment of the preparation method described above of the present invention, the crystallization temperature is 60-200° C. and the time is 1 day to 10 days.

[0035] As shown above, the preparation method of the acoustic enhancement material includes the preparation of silica aerogel reinforced with fibrous structure reinforcing filler and the preparation of acoustic enhancement material, wherein the silica aerogel reinforced with fibrous structure reinforcing filler is prepared by atmospheric pressure drying method, and its preparation process generally includes the dissolution, hydrolysis, polycondensation, aging and drying of silicon source. In the initial stage of the reaction, the silicon source is hydrolyzed to obtain the active monomer silicic acid, and a certain amount of fibrous structure reinforcing filler is added while stirring, and then the silicic acid is polycondensed to generate a polymer (sol) with silicon oxygen (-Si-O-Si-) as the main body, and then cross-linked to form a gel skeleton with a three-dimensional network structure. There are a large number of pores between the gel skeletons, which are filled with solvent molecules such as ethanol and water. The obtained wet gel is first aged, and then the liquid solvent in the gel is replaced by a gaseous substance through a drying process, thereby obtaining a silica aerogel reinforced with a fibrous structure reinforcing filler. In addition, when preparing silica aerogel reinforced with fibrous structure reinforcing fillers, the wet gel can be doped to improve its high temperature stability or the wet gel can be hydrophobically modified to increase its hydrophobicity as needed. The present invention does not make specific requirements on the specific operations of the doping process and the hydrophobic modification process, the process parameters used, the doping substances and the hydrophobic modifiers, etc., and can be reasonably adjusted and selected according to actual needs.

[0036] In addition, according to the actual needs of the on-site operation, the silica aerogel reinforced with the fibrous structure reinforcing filler can be crushed and screened to obtain particles (such as particles with a size of 30-50 mesh), and then the obtained particles are placed in a polyurethane ball mill for rolling ball milling. The collision and friction between the particles are used to remove the sharp edges of the particles to obtain nearly spherical silica aerogel particles reinforced with the fibrous structure reinforcing filler for standby use. After ball milling, the appearance of the acoustic enhancement material is a microsphere of suitable size, which does not require a subsequent molding process and can avoid the introduction of molding adhesives.

[0037] Then, silica aerogel reinforced with a fibrous structure reinforcing filler having an elemental composition similar to that of the molecular sieve is used as a crystallization carrier, which is immersed in a molecular sieve mother liquor containing a silicon source, an alkali source and a mineralizer, and stirred for a sufficiently long time so that the molecular sieve mother liquor can fully wet the silica aerogel; the molecular sieve mother liquor containing the silica aerogel is then transferred to a molecular sieve crystallization device, and appropriate crystallization conditions are set to carry out a crystallization reaction; after the reaction is completed, a microporous-mesoporous-macroporous nano-micro-metastructure acoustic material with regular micropore channels, namely the acoustic enhancement material, can be obtained.

[0038] On the other hand, the present invention also provides a speaker, comprising one or more sound-emitting units and one or more shells, wherein the one or more sound-emitting units are combined with the one or more shells to form a speaker back cavity, wherein at least one of the speaker front cavity, speaker back cavity, shell and sound-emitting unit is equipped with the acoustic enhancement material described above.

[0039] As a specific implementation of the above-mentioned loudspeaker of the present invention, the loudspeaker is a micro loudspeaker.

[0040] As a specific implementation of the loudspeaker described above in the present invention, the sound-emitting unit is an acoustic sensor or the like.

[0041] As a specific embodiment of the speaker described above in the present invention, the acoustic enhancement material can be filled in the rear cavity of the speaker or adhered to the inner wall of the rear cavity of the speaker; the acoustic enhancement material can also be filled in the front cavity of the speaker or adhered to the inner wall of the front cavity of the speaker; the acoustic enhancement material can also be adhered to the inner wall or outer wall of the shell; the acoustic enhancement material can also be adhered to the back of the magnetic bowl of the sound unit and other positions.

[0042] In yet another aspect, the present invention further provides an electronic device, wherein the electronic device comprises the above-mentioned speaker.

[0043] As a specific embodiment of the electronic device described above in the present invention, the electronic device includes a smart phone, TWS earphones, headphones, smart glasses, smart watches, VR devices, AR devices, tablet computers or thin and light laptops, etc.

[0044] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0045] Compared with amorphous materials, SSZ-13 zeolite molecular sieve is an inorganic microporous crystal structure with regular pore distribution. The present invention can introduce a regular microporous structure into amorphous porous materials such as aerogel by compounding SSZ-13 zeolite molecular sieve and silica aerogel reinforced with fibrous structure reinforcing fillers, thereby forming a superstructure material with a microporous-mesoporous-macroporous nanostructure with regular micropores, that is, the acoustic enhancement material provided by the present invention combines the regular microporous structure of SSZ-13 zeolite molecular sieve with the mesoporous and macroporous structures of SiO2 aerogel and the advantages of light weight.

[0046] The acoustic enhancement material provided by the present invention has a pore structure of three scale levels: macropores, mesopores, and micropores, that is, it is an acoustic enhancement material with a nano-micro superstructure. The presence of these pores makes the nano-micro superstructure material have a very large specific surface area. Compared with non-porous materials, these pores can provide a larger area and more sites for the adsorption of air molecules. In the acoustic enhancement material, the pores of the macropores are generally larger than 50nm, the size of the mesopores is between 2-50nm, and the size of the micropores is less than 2nm; and the size of the molecules in the air is all below 1nm, therefore, the macropores and large-sized mesopores in the acoustic enhancement material can allow air molecules to freely enter the pore structure, while the micropores and small-sized mesopores will affect the free diffusion of air molecules. In the process of air molecule diffusion, it is inevitable that they come into contact with the atoms constituting the pore wall and are adsorbed. When the speaker diaphragm vibrates, the diaphragm is compressed inward, which increases the pressure in the rear cavity of the speaker, thereby changing the movement state of air molecules, causing them to quickly enter the porous material, increasing the probability of contact between air molecules and the pore walls, and causing the air molecules to be adsorbed; when the diaphragm vibrates outward, the pressure in the rear cavity of the speaker decreases, and the adsorbed air molecules leave the pore walls due to the pressure difference, changing from an adsorbed state to a desorbed state, and diffuse into large pores or large-sized mesopores; the vibration of the diaphragm causes the pressure in the rear cavity of the speaker to change, thereby causing the state of air molecules in the acoustic enhancement material to continuously change, that is, the state change process is diffusion-adsorption-desorption-diffusion, thereby changing the rigidity of the air in the rear cavity of the speaker, thereby achieving the effect of improving the low-frequency acoustic effect.

[0047] Compared with other molecular sieves with one-dimensional pore structures, the SSZ-13 zeolite molecular sieve used in the present invention is a molecular sieve with a three-dimensional 8-membered ring pore structure. After crystallization on the surface and inside of the silica aerogel reinforced with a fibrous structure reinforcing filler, it has a significant effect on improving the porosity, accessible volume and specific surface area of ​​the final acoustic enhancement material. Therefore, the low-frequency acoustic improvement effect of the acoustic enhancement material provided by the present invention is significantly better than that of the existing acoustic enhancement materials.

[0048] In addition, the acoustic enhancement material provided by the present invention contains silica aerogel reinforced with fibrous structure reinforcing fillers. The introduction of the fibrous structure reinforcing fillers enhances the structural strength of the SiO2 aerogel. Furthermore, the present invention does not require a subsequent molding process when preparing the acoustic enhancement material, and can avoid the introduction of molding adhesives. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0050] Figure 1 This is a scanning electron microscope image of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 of the present invention.

[0051] Figure 2 This is a scanning electron microscope image of the acoustic enhancement material prepared in Example 1 of the present invention.

[0052] Figure 3 This is a scanning electron microscope image of the acoustic enhancement material prepared in Comparative Example 1.

[0053] Figure 4 This is the micropore distribution diagram of the acoustic enhancement material prepared in Example 1 of the present invention.

[0054] Figure 5 This is the mesopore distribution diagram of the acoustic enhancement material prepared in Example 1 of the present invention.

[0055] Figure 6 This is the macropore distribution diagram of the acoustic enhancement material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0056] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0057] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0058] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0059] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0060] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0061] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0062] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0063] Preparation Example 1

[0064] This preparation example provides a halloysite fiber reinforced silica aerogel microsphere, which is prepared by a preparation method comprising the following specific steps:

[0065] Take tetraethyl orthosilicate as silicon source, deionized water as solvent, anhydrous ethanol as cosolvent (to increase the solubility of tetraethyl orthosilicate in deionized water), oxalic acid as acid catalyst, ammonia water as alkaline catalyst and formamide as gel promoter. First, weigh deionized water, anhydrous ethanol and tetraethyl orthosilicate in order according to the molar ratio of 10:5:1 and mix them, transfer the mixed solution to a 45°C water bath, add 0.1M oxalic acid solution dropwise during stirring until pH=2, and stir for 30 minutes. During this process, tetraethyl orthosilicate is hydrolyzed to produce sol; then add formamide dropwise, the molar ratio of formamide to tetraethyl orthosilicate is 0.7:1, stir for 5-10 minutes while adding formamide, add 3wt% of halloysite fiber with a length of 800nm-1.2μm (the amount is calculated based on the SiO2 content in tetraethyl orthosilicate) during stirring and mix them evenly, wherein halloysite is a kind of aluminum oxide. The aluminosilicate material composed of and silicon oxide has high thermal stability and corrosion resistance; fibrous halloysite is added to the mother liquor used to prepare silica aerogel, and it can participate in the sol-gel process of silica aerogel; then, a 0.5M ammonia solution is added until the pH is 7, and after stirring evenly, it is allowed to stand to produce gel, and a wet gel can be obtained when the liquid surface does not flow at an angle of 45°; a 50v% ethanol solution is added to the wet gel, and the liquid level is higher than the wet gel, and the wet gel is aged for 24h; finally, the aged wet gel is staged dried, that is, first dried at 60°C for 4h and then dried at 80°C for 8h, to obtain a silica aerogel reinforced with halloysite fibers.

[0066] The prepared halloysite fiber reinforced silica aerogel is crushed into fine particles; the crushed particles are screened with a sieve to obtain microparticles with a size of 30-40 mesh; the particles are then transferred to a polyimide ball mill for ball milling, and the friction and collision between the particles are used to remove the irregular edges of the particles to obtain ellipsoidal or spherical particles; finally, the particles are screened again to obtain approximately spherical halloysite fiber reinforced silica aerogel particles / microparticles with a size of 35-50 mesh, and are placed in a room temperature dryer for use.

[0067] Preparation Example 2

[0068] This preparation example provides a 35-50 mesh size halloysite fiber reinforced silica aerogel microsphere, and the preparation method thereof differs from the preparation method in Preparation Example 1 only in that:

[0069] 10% of halloysite fibers were introduced.

[0070] Comparative Preparation Example 1

[0071] This comparative preparation example provides an unreinforced silica aerogel microsphere with a size of 35-50 mesh, and the preparation method thereof differs from the preparation method in Preparation Example 1 only in that:

[0072] Halloysite fibers were not introduced.

[0073] Example 1

[0074] This embodiment provides an acoustic enhancement material, which is prepared by a preparation method comprising the following specific steps:

[0075] Silica sol (SiO2 accounting for 30wt%) is used as a silicon source, aluminum hydroxide is used as an aluminum source, sodium hydroxide is used as an alkali source and a mineralizer, deionized water is used as a solvent, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is used as an organic template;

[0076] The specific preparation process is as follows: weigh 1.80g of NaOH and dissolve it in 25.0mL of deionized water, then add the resulting solution dropwise into 19.04g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution with a mass concentration of 25wt% under stirring, and stir evenly to obtain solution A; add 0.078g of aluminum hydroxide to solution A, and after the aluminum hydroxide is completely dissolved, a uniform solution B is formed; add 30.0g of the above-mentioned silica sol to solution B, and during the addition process, pay attention to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol-like state, the stirring speed is reduced; then wash the silica sol container with 40.0mL of deionized water, and add the washing liquid to solution B, and continue stirring at room temperature for 1.0h to obtain a mixed solution C, that is, the preparation of the molecular sieve mother liquor is completed;

[0077] Subsequently, 15.0 g of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 were added to the molecular sieve mother liquor, and stirring was continued for 1 hour. The resulting mixed solution was then transferred to a PTFE-lined reactor, aged at 80°C for 24 hours, and then crystallized at 170°C for 48 hours; after the crystallization, the resulting crystallized product was centrifuged and washed several times to obtain a nano-micro super-structure acoustic material, which was then dried overnight at 100°C and then calcined at 500°C for 6 hours to obtain a nano-micro super-structure acoustic material with the template removed, i.e., the acoustic enhancement material. According to the mass change of the material before and after crystallization, the mass ratio of the crystallized molecular sieve, i.e., SSZ-13 zeolite molecular sieve, to the halloysite fiber-reinforced silica aerogel microspheres is 2.75:5.

[0078] Example 2

[0079] This embodiment provides an acoustic enhancement material, which is prepared by a preparation method comprising the following specific steps:

[0080] Silica sol (SiO2 accounting for 30wt%) is used as a silicon source, aluminum hydroxide is used as an aluminum source, sodium hydroxide is used as an alkali source and a mineralizer, deionized water is used as a solvent, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is used as an organic template;

[0081] The specific preparation process is as follows: weigh 1.80g of NaOH and dissolve it in 25.0mL of deionized water, then add the resulting solution dropwise into 19.04g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution with a mass concentration of 25wt% under stirring, and stir evenly to obtain solution A; add 0.078g of aluminum hydroxide to solution A, and after the aluminum hydroxide is completely dissolved, a uniform solution B is formed; add 30.0g of the above-mentioned silica sol to solution B, and during the addition process, pay attention to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol-like state, the stirring speed is reduced; then wash the silica sol container with 40.0mL of deionized water, and add the washing liquid to solution B, and continue stirring at room temperature for 1.0h to obtain a mixed solution C, that is, the preparation of the molecular sieve mother liquor is completed;

[0082] Subsequently, 15.0 g of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 2 were added to the molecular sieve mother liquor, and stirring was continued for 1 hour. The resulting mixed solution was then transferred to a PTFE-lined reactor, aged at 80°C for 24 hours, and then crystallized at 170°C for 48 hours; after the crystallization, the resulting crystallized product was centrifuged and washed several times to obtain a nano-micro super-structure acoustic material, which was then dried overnight at 100°C and then calcined at 500°C for 6 hours to obtain a nano-micro super-structure acoustic material with the template removed, i.e., the acoustic enhancement material. According to the mass change of the material before and after crystallization, the mass ratio of the crystallized molecular sieve, i.e., SSZ-13 zeolite molecular sieve, to the halloysite fiber-reinforced silica aerogel microspheres is 2.78:5.

[0083] Comparative Example 1

[0084] This comparative example provides an acoustic enhancement material, which is prepared by a preparation method comprising the following specific steps:

[0085] Silica sol (SiO2 accounting for 30wt%) is used as a silicon source, aluminum hydroxide is used as an aluminum source, sodium hydroxide is used as an alkali source and a mineralizer, deionized water is used as a solvent, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is used as an organic template;

[0086] The specific preparation process is as follows: weigh 1.80g of NaOH and dissolve it in 25.0mL of deionized water, then add the resulting solution dropwise into 19.04g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution with a mass concentration of 25wt% under stirring, and stir evenly to obtain solution A; add 0.078g of aluminum hydroxide to solution A, and after the aluminum hydroxide is completely dissolved, a uniform solution B is formed; add 30.0g of the above-mentioned silica sol to solution B, and during the addition process, pay attention to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol-like state, the stirring speed is reduced; then wash the silica sol container with 40.0mL of deionized water, and add the washing liquid to solution B, and continue stirring at room temperature for 1.0h to obtain a mixed solution C, that is, the preparation of the molecular sieve mother liquor is completed;

[0087] The obtained molecular sieve mother liquor is then transferred to a PTFE-lined reactor, first aged at 80°C for 24 hours, and then crystallized at a constant temperature of 170°C for 48 hours; after the crystallization is completed, the obtained crystallized product is centrifuged and washed multiple times, then dried overnight at 100°C, and then calcined at 500°C for 6 hours to obtain the molecular sieve powder material with the template removed, namely the acoustic enhancement material.

[0088] Comparative Example 2

[0089] This comparative example provides an acoustic enhancement material, which is prepared by a preparation method comprising the following specific steps:

[0090] Silica sol (SiO2 accounting for 30wt%) is used as a silicon source, sodium hydroxide is used as an alkali source and a mineralizer, deionized water is used as a solvent, and hexamethyleneimine hydrochloride and N,N,N-trimethyl-1-adamantyl ammonium hydroxide are used as organic templates;

[0091] The specific preparation process is as follows: weigh 7.0g of hexamethyleneimine hydrochloride, dissolve it in 65.0mL of deionized water, then add the obtained solution dropwise into 35.18g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution with a mass concentration of 25wt% under stirring, and stir evenly to obtain solution A; add 33.33g of the above-mentioned silica sol to solution A, and pay attention to adjusting the stirring speed during the addition process. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol-like state, the stirring speed is reduced; then wash the silica sol container with 40.0mL of deionized water, and add the washing liquid to solution A. After stirring evenly, adjust the solution pH to between 11.2 and 11.5 with 0.1M NaOH; then continue stirring at room temperature for 1.0h to obtain a mixed solution B, that is, the preparation of the molecular sieve mother liquor is completed;

[0092] Subsequently, 16.0 g of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 were added to the molecular sieve mother liquor, and stirring was continued for 1 hour, and then the resulting mixed solution was transferred to a PTFE-lined reactor and crystallized at a constant temperature of 150°C for 10 days; after the crystallization, the resulting crystallized product was centrifuged and washed several times to obtain a nano-micro superstructure acoustic material, which was then dried overnight at a temperature of 100°C and then calcined at a high temperature of 500°C for 6 hours to obtain a nano-micro superstructure acoustic material / acoustic improvement material with a nano-micro superstructure after the template agent was removed, that is, the acoustic enhancement material. According to the mass change of the material before and after crystallization, the mass ratio of the crystallized molecular sieve, that is, the MCM-35 zeolite molecular sieve and the halloysite fiber-reinforced silica aerogel microspheres is 4.81:8.

[0093] Characterization Test Example 1

[0094] In this characterization test example, the halloysite fiber reinforced silica aerogel microspheres prepared in Preparation Example 1, the acoustic enhancement material prepared in Example 1 and the acoustic enhancement material prepared in Comparative Example 1 were analyzed by scanning electron microscope, and the experimental results obtained were as follows: Figure 1-Figure 3 As shown. Among them, Figure 1 This is a scanning electron microscope image of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1. Figure 1 It can be seen that after ball milling, the particles have nearly spherical appearance and the particle size is about 300 μm; Figure 2 The figure is a scanning electron microscope image of the acoustic enhancement material prepared in Example 1. When preparing the material, the silica aerogel microspheres reinforced by halloysite fibers are used as carriers, and the SSZ-13 zeolite molecular sieve is crystallized on the inner and outer surfaces of the carrier. After crystallization, the surface of the silica aerogel particles reinforced by the halloysite fibers becomes somewhat rough, and the particle size increases. The acoustic enhancement material of Comparative Example 1 does not introduce aerogel microspheres during the preparation process, and the obtained SSZ-13 molecular sieve particles are ellipsoidal in shape, with a size of less than 5 μm, as shown in FIG. Figure 3 shown.

[0095] Characterization Test Example 2

[0096] This characterization test example investigates the pore size distribution of the acoustic enhancement material prepared in Example 1. The obtained micropore distribution diagram, mesopore distribution diagram and macropore distribution diagram are shown in Figure 1. Figure 4-Figure 6 As shown. Figure 4 It can be seen that the acoustic enhancement material has micropores, the size of which is between 0.45-0.6nm, with 0.47nm being the most distributed. Figure 5 It can be seen that the acoustic enhancement material has mesopores, and the mesopore sizes are mostly distributed at 2.1nm, 2.6nm and 2.9nm; Figure 6It can be seen that the acoustic enhancement material also has macropores within 100 μm, but most of the macropores are within 50 μm.

[0097] Performance Test Example 1

[0098] In this embodiment, the strength of the halloysite fiber reinforced silica aerogel particles prepared in Preparation Example 1-Preparation Example 2, the acoustic enhancement material prepared in Example 1-Example 2, the unreinforced silica aerogel microspheres prepared in Comparative Preparation Example 1, and the acoustic enhancement material provided in Comparative Example 2 were tested in accordance with the provisions of Standard T / CECA 78-2022 "Porous Sound-Absorbing Particles for Micro Speakers". The strength test results are shown in Table 1 below.

[0099] Table 1

[0100]

[0101]

[0102] According to the strength test results shown in Table 1 above, compared with the unreinforced (i.e., no reinforcing fiber introduced) silica aerogel microspheres prepared in Comparative Preparation Example 1, the silica aerogel microspheres reinforced with halloysite fibers prepared in Preparation Example 1 have higher particle strength. Increasing the content of halloysite fibers will improve the particle strength of the silica aerogel microspheres to a certain extent. Specifically, the microspheres provided in Preparation Example 2 are silica aerogel microspheres reinforced with 10%wt of halloysite fibers, which have correspondingly stronger particle strength than Comparative Preparation Example 1 and Preparation Example 1.

[0103] After the SSZ-13 zeolite molecular sieve is crystallized on the surface and inside of the silica aerogel microspheres reinforced by halloysite fibers, the particle strength of the acoustic enhancement material finally obtained will also be improved. Specifically, Examples 1 and 2 of the present invention prepare acoustic enhancement materials based on the silica aerogel microspheres reinforced by halloysite fibers provided in Preparation Examples 1 and 2, respectively. Compared with the silica aerogel microspheres reinforced by halloysite fibers provided in Preparation Examples 1 and 2, the particle strength of the acoustic enhancement materials provided in Examples 1 and 2 is improved, that is, after the SSZ-13 zeolite molecular sieve is crystallized on the surface and inside of the silica aerogel microspheres reinforced by halloysite fibers, the particle strength of the acoustic enhancement material finally obtained will be improved.

[0104] Comparative Example 2: Based on the halloysite fiber-reinforced silica aerogel microspheres provided in Preparation Example 1, an acoustic enhancement material is prepared. Compared with Preparation Example 1, the particle strength of the acoustic enhancement material provided in Comparative Example 2 is also improved, which indicates that after the MCM-35 molecular sieve is crystallized on the surface and inside of the halloysite fiber-reinforced silica aerogel microspheres, the particle strength of the final acoustic enhancement material is also improved. Compared with the acoustic enhancement materials provided in Examples 1 and 2 of the present invention, there is no obvious difference in the particle strength of the acoustic enhancement material obtained by introducing the MCM-35 molecular sieve in Comparative Example 2.

[0105] Performance Test Example 2

[0106] In this embodiment, the water absorption rates of the halloysite fiber reinforced silica aerogel particles prepared in Preparation Example 1-Preparation Example 2, the acoustic enhancement materials prepared in Example 1-Example 2, the unreinforced silica aerogel microspheres prepared in Comparative Preparation Example 1, and the acoustic enhancement materials prepared in Comparative Example 1-Comparative Example 2 were tested in accordance with the provisions of the standard T / CECA 78-2022 "Porous Sound-Absorbing Particles for Micro Speakers". The water absorption test results are shown in Table 2 below.

[0107] Table 2

[0108] M1 / g M2 / g Water absorption / % Preparation Example 1 2.001 2.018 0.85 Preparation Example 2 2.001 2.037 1.80 Comparative Preparation Example 1 2.001 2.017 0.80 Example 1 2.002 2.011 0.45 Example 2 2.000 2.019 0.95 Comparative Example 1 2.002 2.010 0.40 Comparative Example 2 2.001 2.010 0.45

[0109] According to the water absorption test results shown in Table 2 above, it can be seen that the silica aerogel microspheres reinforced with an appropriate amount of halloysite fibers (Preparation Example 1), the unreinforced silica aerogel microspheres (Comparative Preparation Example 1) and the silica aerogel microspheres reinforced with an excess of halloysite fibers (Preparation Example 2) all have high water absorption. This is mainly because the presence of silanol groups in the silica aerogel gives it a high water absorption rate. At the same time, halloysite is a material with a low silicon-aluminum ratio and is also a material with a good affinity for water. Therefore, the excessive introduction of halloysite will lead to a significant increase in the overall water absorption of the material.

[0110] Since the acoustic enhancement materials provided in Examples 1 and 2 include halloysite fiber-reinforced silica aerogel microspheres and SSZ-13 zeolite molecular sieves, the SSZ-13 zeolite molecular sieves are chemically bonded to the interior and surface of the halloysite fiber-reinforced silica aerogel microspheres, and the SSZ-13 zeolite molecular sieves have excellent hydrophobicity, the water absorption rate of the acoustic enhancement materials provided in Examples 1 and 2 is lower than that of the halloysite fiber-reinforced silica aerogel microspheres provided in Preparation Examples 1 and 2, respectively.

[0111] From the water absorption data of the acoustic enhancement materials provided in Example 1 and Example 2, it can be seen that due to the high water absorption of the silica aerogel microspheres reinforced with excess halloysite fibers provided in Preparation Example 2, the water absorption of the acoustic enhancement material provided in Example 2 is also significantly higher than that of the acoustic enhancement material provided in Example 1. Comparative Example 2 introduces pure silicon MCM-35 molecular sieve to prepare an acoustic enhancement material based on Preparation Example 1. Since pure silicon MCM-35 molecular sieve has good hydrophobicity, the acoustic enhancement material provided in Comparative Example 2 has a very close water absorption to that of the acoustic enhancement material provided in Example 1.

[0112] Performance Test Example 3

[0113] In this embodiment, the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Examples 1-2, the acoustic enhancement materials prepared in Examples 1-2, the unreinforced silica aerogel microspheres prepared in Comparative Preparation Example 1, and the acoustic enhancement materials prepared in Comparative Examples 1-2 were first filled into a standard sound cavity (the volume of the sound cavity was 1.0 cubic centimeters, the specific structure of the sound cavity can be referred to CN215072984U, and the filling amount of the sound-absorbing material to be tested was 300 mg), and then the acoustic performance tests were performed on them respectively, wherein the acoustic performance The test is carried out by conventional methods in the art. For example, the acoustic performance of each sample to be tested is tested by referring to the "Measurement of Electrical Impedance" method shown in paragraphs 0049-0054 of Chinese patent application CN105049997A. Specifically, each sample to be tested is tested according to the "Measurement of Electrical Impedance" method to obtain an electrical impedance spectrum. The curve in the electrical impedance spectrum corresponds to the electrical impedance curve, wherein the frequency corresponding to the highest point of the electrical impedance curve is F0. When the sample to be tested is not loaded in the speaker, the measured F0 is marked as F 0-空腔 When the speaker is loaded with each sample to be tested, the measured F0 is marked as F 0-待测样品 , then the calculation formula of ΔF0 is:

[0114] ΔF0=F 0-空腔 -F 0-待测样品 .

[0115] The test signal used in the acoustic performance test process is the analog program signal or pink noise signal specified in GB / T 12060.1.

[0116] The test results obtained in this embodiment are shown in Table 3.

[0117] Table 3

[0118]

[0119] According to the acoustic performance test results shown in Table 3 above, the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 can achieve a certain low-frequency acoustic improvement effect. Compared with the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1, when the halloysite fiber is not introduced as a reinforcing filler, the low-frequency acoustic improvement effect of the silica aerogel microspheres is not improved in Comparative Preparation Example 1. Preparation Example 2 introduces an excessive amount of halloysite fiber reinforcing filler, and the low-frequency acoustic improvement effect of the halloysite fiber-reinforced silica aerogel microspheres obtained therefrom is slightly decreased compared with Preparation Example 1 and Comparative Preparation Example 1.

[0120] Compared with the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Examples 1-2 and the silica aerogel microspheres prepared in Comparative Preparation Example 1, the acoustic enhancement material prepared by using molecular sieve powder alone in Comparative Example 1 has an improved low-frequency acoustic improvement effect. Comparative Example 2 is based on the halloysite fiber-reinforced silica aerogel microspheres provided in Preparation Example 1, and MCM-35 molecular sieves are introduced by the template method to prepare an acoustic enhancement material. Compared with the halloysite fiber-reinforced silica aerogel microspheres provided in Preparation Example 1, the acoustic enhancement material provided in Comparative Example 2 also has an improved low-frequency acoustic improvement effect. However, compared with SSZ-13 zeolite molecular sieve (which is a molecular sieve with a three-dimensional 8-membered ring pore structure), MCM-35 molecular sieve is a molecular sieve with a one-dimensional 8-membered ring pore structure, and the porosity, accessible volume, specific surface area, etc. are all low. After crystallization on the surface and inside of the halloysite fiber-reinforced silica aerogel microspheres, the improvement effect on the porosity, accessible volume and specific surface area of ​​the final acoustic enhancement material is limited, so the acoustic enhancement material provided in Comparative Example 2 has limited improvement on the low-frequency acoustic effect. Specifically, the low-frequency acoustic improvement effect of the acoustic enhancement material provided in Comparative Example 2 is significantly worse than that of the acoustic enhancement material provided in Example 1.

[0121] Compared with the acoustic enhancement materials obtained in Comparative Examples 1 and 2, in Examples 1 and 2 of the present invention, the molecular sieve mother solution is crystallized on the surface and inside of the silica aerogel microspheres reinforced with halloysite fibers to obtain nano-micro superstructure materials with micropores, mesopores and macropores, so that the acoustic enhancement materials prepared therefrom have excellent low-frequency acoustic improvement effects. However, Example 2 uses an excess of halloysite fiber-reinforced silica aerogel microspheres to prepare nano-micro superstructure acoustic enhancement materials. Compared with Example 1, the low-frequency acoustic improvement effect of the nano-micro superstructure acoustic enhancement material provided by Example 2 is reduced, which indicates that the introduction of excessive halloysite fiber-reinforced fillers will slightly reduce the low-frequency acoustic improvement effect of the obtained nano-micro superstructure acoustic enhancement material.

[0122] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. An acoustic enhancement material, characterized in that: The acoustic enhancement material has micropores, mesopores and macropores, and includes silica aerogel reinforced with fibrous structure reinforcement filler and SSZ-13 zeolite molecular sieve, wherein the SSZ-13 zeolite molecular sieve is chemically bonded to the interior and surface of the silica aerogel reinforced with fibrous structure reinforcement filler.

2. The acoustic enhancement material according to claim 1, characterized in that: The mass ratio of the SSZ-13 zeolite molecular sieve to the silica aerogel reinforced with the fibrous structure reinforcing filler is 1:1-1:

4.

3. The acoustic enhancement material according to claim 1 or 2, characterized in that: The SSZ-13 zeolite molecular sieve includes a pure silicon structure molecular sieve, a silicon aluminum structure molecular sieve, a silicon phosphorus aluminum structure molecular sieve or a phosphorus aluminum structure molecular sieve.

4. The acoustic enhancement material according to claim 1, characterized in that: Taking the total weight of SiO2 in the silica aerogel reinforced with the fibrous structure reinforcing filler as 100%, the content of the fibrous structure reinforcing filler is 1-8%.

5. The acoustic enhancement material according to claim 1 or 4, characterized in that: The silica aerogel reinforced with a fibrous structure reinforcing filler comprises a fibrous structure reinforcing filler and a silica aerogel, wherein the fibrous structure reinforcing filler is uniformly dispersed in the silica aerogel.

6. The acoustic enhancement material according to claim 1 or 4, characterized in that: The size of the silica aerogel reinforced with the fibrous structure reinforcing filler is 35-50 meshes.

7. The acoustic enhancement material according to claim 1 or 2, characterized in that: The fibrous structure reinforcing filler includes one or a combination of halloysite, boehmite, mullite and asbestos.

8. The method for preparing the acoustic enhancement material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Dissolving a silicon source, an alkali source and a mineralizer in deionized water to obtain a molecular sieve mother liquor; The silica aerogel reinforced with a fibrous structure reinforcing filler is added to the molecular sieve mother solution and mixed evenly, the obtained mixed solution is crystallized, and finally the crystallized product is washed, dried and calcined to obtain the acoustic enhancement material.

9. The preparation method according to claim 8, characterized in that: The molecular sieve mother solution also contains a template.

10. The preparation method according to claim 8 or 9, characterized in that: The preparation method of the silica aerogel reinforced with the fibrous structure reinforcing filler comprises: A silicon source, a co-solvent and deionized water are mixed to obtain a first mixed liquid, an acidic catalyst is added to the first mixed liquid to hydrolyze the silicon source to produce a sol, a gel accelerator and a fibrous structure reinforcing filler are then added to the sol and mixed evenly to obtain a second mixed liquid, an alkaline catalyst is then added to the second mixed liquid to form a wet gel, and finally the wet gel is aged and dried to obtain the silica aerogel reinforced with the fibrous structure reinforcing filler.

11. The preparation method according to claim 10, characterized in that: The silicon source is organic silicon and / or inorganic silicon, wherein the organic silicon includes one or a combination of ethyl orthosilicate, methyl orthosilicate, polysiloxane, methyltrimethoxysilane, methyltriethoxysilane and silsesquioxane, and the inorganic silicon includes one or a combination of silica sol, water glass, sodium silicate and silicon tetrachloride.

12. The preparation method according to claim 8 or 9, characterized in that: The crystallization temperature is 60-200° C., and the crystallization time is 1 day to 10 days.

13. A speaker, comprising one or more sound-emitting units and one or more shells, wherein the one or more sound-emitting units and the one or more shells are combined to form a speaker rear cavity, characterized in that: At least one of the speaker front cavity, the speaker rear cavity, the shell and the sound-emitting unit is equipped with the acoustic enhancement material according to any one of claims 1 to 7.

14. The loudspeaker according to claim 13, characterized in that The speaker is a micro speaker.

15. An electronic device, characterized in that: The electronic device comprises the speaker according to claim 13 or 14.

16. The electronic device according to claim 15, characterized in that: The electronic device includes a smart phone, a TWS headset, a head-mounted headset, smart glasses, a smart watch, a VR device, an AR device, a tablet computer or a thin and light laptop computer.

Citation Information

Patent Citations

  • Loudspeaker system with improved sound

    CN103098490A

  • Loudspeaker System with Improved Sound

    CN105049997A

  • A silicon dioxide aerogel sound absorption material and a sound production device

    CN109874089A

  • Acoustic material testing tool assembly

    CN215072984U

  • A method for synthesizing Y-type mesoporous zeolite

    CN102259889A

Cited By

  • Sound production device and electronic equipment

    CN120583355A